2009
DOI: 10.1038/ajg.2008.126
|View full text |Cite
|
Sign up to set email alerts
|

Serum Ferritin as a Predictor of Treatment Outcome in Patients With Chronic Hepatitis C

Abstract: In CHC, SF is a useful marker for assessing disease duration and progression before starting treatment and for predicting therapeutic response while on therapy. SF rise during antiviral therapy is largely independent of hemolysis and likely indicates activation of macrophages in response to antivirals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1
1

Year Published

2010
2010
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 40 publications
2
21
1
1
Order By: Relevance
“…The increased ratio of serum ferritin (serum ferritin/ baseline ferritin ratio) in SVR subjects was significantly higher than in non-SVR individuals. A similar report has been previously published, and its results correspond with what we are reporting here [18] .…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The increased ratio of serum ferritin (serum ferritin/ baseline ferritin ratio) in SVR subjects was significantly higher than in non-SVR individuals. A similar report has been previously published, and its results correspond with what we are reporting here [18] .…”
Section: Discussionsupporting
confidence: 82%
“…Though we did not investigate parameters involving hemolysis or RBV concentration, the correlation between rising levels of ferritin and the rate of SVR may be related to RBV-induced hemolysis and/or RBV concentration. Ferrara et al [18] considered that the rise of serum ferritin correlated to RBV-induced hemolysis at earlier phases of treatment, but the correlation between serum ferritin levels and hemolysis is lost at later phases of treatment. Therefore, they considered that elevated serum ferritin at a later phase might be caused by a reactive response from activated macrophages to interferon [18] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has long been recognized that iron overload promotes hepatic fibrosis in hereditary hemochromatosis (reviewed by Drakesmith and Prentice, 2008). Serum iron stores are increased frequently in patients with chronic hepatitis C and elevated hepatic iron concentration has been associated with a poor response to interferon alfa [Ferrara et al, 2009]. In the present study, HFE gene mutations were assessed retrospectively in a large cohort of well-characterized chronic hepatitis C patients.…”
Section: Discussionmentioning
confidence: 98%
“…Patients with the C282Y mutation had more-advanced hepatic fibrosis and decompensated liver disease more frequently in the case of concomitant chronic hepatitis C than patients without this mutation [Hezode et al, 1999;Bonkovsky et al, 2002;Erhardt et al, 2003;Pacal et al, 2007;Won et al, 2009]. Recently, Ferrara et al [2009] showed that serum ferritin is a predictor of treatment outcome in patients with chronic hepatitis C.…”
Section: Introductionmentioning
confidence: 96%